Analysis of Financial Management and Subjective Well-Being of Bank Emok Customer Families in Bandung City, West Java - Ajrania, Sri; Sunarti, Euis; Herawati, Tin (International Journal of Economics (IJEC), 2023)
Facing rising prices requires effective financial management to improve family welfare. Low income and having difficulty making ends meet can often cause people to go into debt. It is essential to achieve a good balance between income and debt by understanding the limits of one's ability to pay and utilizing debt wisely for productive purposes. The purpose of the study was to gain an understanding of family characteristics and debt characteristics that become Bank Emok customers and analyze the relationship and influence of family characteristics, debt characteristics, financial management and subjective welfare. This study used a purposive cross-sectional study design with respondents of as many as 60 wives from complete families who became customers of Bank Emok. The results of the relationship test (correlation) showed that the age of the wife was significantly negatively associated with financial management. The length of marriage was significantly positively related to the amount of debt. Income is completely considerably associated with financial management and subjective well-being. The results of the influence test with Structural Equation Modeling show that the application of sound financial management practices can make a positive contribution to emotional well-being (β= 0.561**; t > 1.96).